Analysis of Multi-hop Wireless Sensor Networks using Probability Propagation Models - Komgrit Jaksukam; Teerawat Tongloy; Santad Chuwongin; Siridech Boonsang (My University, 2019)
This paper presents a formula for estimating the probability of collecting a given amount of data from a propagation model and multi-hop wireless sensor networks (WSNs) based on Monte Carlo simulation with cluster-tree topology. The probabilistic model is based on an analytical model of the IEEE 802.15.4 MAC protocol. The probability of successful node transmission is extended to the probabilities of successful collection at the cluster P(X=k) and sink node P(X ≥ k). A numerical example has been provided for comparing the probabilities. We propose a model to calculate the probability from the ratio of the collection rate to the total number of nodes and therefore provide the likeliness of complete data collection. Finally, the results from our analysis provide an estimation of the probability of achieving successful transmission in WSNs.
Keywords: Coverage probability; Energy Efficient Wireless Sensor Networks